2019
DOI: 10.3389/fonc.2019.00415
|View full text |Cite
|
Sign up to set email alerts
|

Validation of CyTOF Against Flow Cytometry for Immunological Studies and Monitoring of Human Cancer Clinical Trials

Abstract: Flow cytometry is a widely applied approach for exploratory immune profiling and biomarker discovery in cancer and other diseases. However, flow cytometry is limited by the number of parameters that can be simultaneously analyzed, severely restricting its utility. Recently, the advent of mass cytometry (CyTOF) has enabled high dimensional and unbiased examination of the immune system, allowing simultaneous interrogation of a large number of parameters. This is important for deep interrogation of immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 31 publications
1
125
0
1
Order By: Relevance
“…To extensively characterize the differences in immune profiles, we utilized CyTOF that allows simultaneous staining of cells isolated from tumor tissue/naïve brain with 31 metal-conjugated antibodies 21 . We confirmed CyTOF staining by flow cytometry 27 and found no difference in proportions of CD4/CD8 and Tim3+ CD4/CD8 T cells in mouse tumor samples ( Supplementary Fig. 5).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…To extensively characterize the differences in immune profiles, we utilized CyTOF that allows simultaneous staining of cells isolated from tumor tissue/naïve brain with 31 metal-conjugated antibodies 21 . We confirmed CyTOF staining by flow cytometry 27 and found no difference in proportions of CD4/CD8 and Tim3+ CD4/CD8 T cells in mouse tumor samples ( Supplementary Fig. 5).…”
Section: Resultssupporting
confidence: 70%
“…Flow cytometry with isolated TIICs is the most reliable method for immune-phenotyping and has been used frequently for identifying immune cell populations and their activation status. One of the major limitations with studying immune-cell subsets in brain tumors by regular flow cytometry is the limited number of fluorescent channels that can be analyzed at a time that gets further complicated by compensation issues resulting in multiple separate antibody cocktails 41 . As the number of TIICs isolated from the brain is low which limits the ability of flow cytometry to phenotype, CyTOF provides an excellent alternative as a large number of immune-cell population defining markers can be analyzed simultaneous, without any drop off in signal sensitivity 21 .…”
Section: Discussionmentioning
confidence: 99%
“…These issues can be overcome by following precise rules applicable to panel design, and optimized panels published such as Optimized Multicolor Immunophenotyping Panels (OMIPs) (67)(68)(69)(70)(71)(72). Together with fluorescent flow cytometry, mass cytometry (also called CyTOF-Cytometry by Time-Of-Flight) is a technology that allows simultaneous analysis of more than 40 different molecules, including cytokines and transcription factors, with minimal compensation (53,54). This technique exploits the use of monoclonal antibodies conjugated with heavy-metal isotopes to stain cells and quadrupole time-of-flight mass spectrometer to perform the detection (73).…”
Section: High-parameter Flow Cytometrymentioning
confidence: 99%
“…CyTOF is particularly valuable when analyzing samples with a limited number of cells such as pediatric patients or tumor biopsies. In a recent report, Gadalla and colleagues demonstrated that using a 40+ parameter panel on peripheral blood mononuclear cell (PBMC) and tumor tissue samples, CyTOF is as effective as mFC for the identification of diverse cell subsets and their subsequent phenotyping (33).…”
Section: Overview Of Current High-throughput Technologies For Systemsmentioning
confidence: 99%